The Effect of Regional Income, Leverage, Regional Property on Internet Financial Reporting Disclosure - Iszardani, Cindy Gustiara; Hardiningsih, Pancawati (Jurnal Analisis Bisnis Ekonomi, 2021)
This study aims to analyze the effect of local revenue, leverage, local government wealth on the disclosure of web-based local government financial statements. The population and sample of this study are the regional government financial reports of Central Java Province which consist of 29 districts and 6 cities for the 2015-2018 fiscal year which have been audited by the BPK. The analysis method uses a multiple regression panel data model with the Eviews 9 application. The results of this study indicate that local revenue and general allocation funds have a significant positive effect on the disclosure of web-based local government financial reports. However, the wealth of the local government in turn has a negative effect on the disclosure of web-based local government financial reports. Meanwhile, leverage has no effect on the disclosure of web-based local government financial statements. The results of this study can be used as a consideration for the government informing regulations, rewards, and sanctions in order to increase the transparency of digital financial reports.